Pelaksanaan Eksekusi Riil terhadap Tanah dan Bangunan dalam Penyelesaian Perkara Perdata (Studi Penetapan Ketua Pengadilan Negeri Madiun Kelas 1B Nomor 02/Pen.Pdt.Eks/2021/ PN Mad) - Gilang Setiawan; Shailawa Ramb Madani; Brina Saskya Paramita; Lintang Yudhantaka (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Executions often occur due to land disputes. The emergence of a land dispute can occur due to a lawsuit from a person or legal entity that contains a lawsuit for torts that have harmed the plaintiff's land rights. Like the real execution referred to in Article 1033 Rv is the execution of a judge's judgment ordering the emptying of fixed objects. This research is normative and empirical legal research, namely literature legal research that refers to legal norms contained in laws and regulations and field research to obtain information as supporting material, especially matters that affect the process of legal work in the implementation of real executions by the Madiun District Court. The process of carrying out real execution can be carried out if in a case there are parties who are negligent or unwilling to carry out court decisions voluntarily, this is based on Article 1033 Rv, Article 200 paragraph (11) HIR, and Article 218 paragraph (2) Rbg. In this paper, it is expected to provide a real picture of how the real execution of unlawful acts in the Madiun District Court Class I B. Execution is carried out on the basis of an application execution of execution. On the existence of the said petition the Chief Justice of Madiun District Court for his authority gave a reprimand (aanmaning) to the execution respondent. From the author's analysis, the execution was in accordance with the implementation of the execution by the Madiun District Court.